(untitled) (Eurasian Medical Research Periodical, 2026)
Measles is a highly contagious disease of viral etiology. To this day, the measles remains one of the main causes of death in younger age groups, even despite many years of positive experience in using an effective live measles vaccine. With the ongoing complication of the epidemiological situation regarding the measles, both in the country and globally, it seems appropriate to study the immune layer to the measles virus in various gender, age, and social groups and to identify risk groups most susceptible to infection. According to our observations, in most cases, 94.4% of cases of measles proceeded in a typical moderate form. The typical moderate form of measles was characterized by a cyclical course with a change in classical periods, the presence of characteristic clinical syndromes of the disease. Pathognomonic symptoms for measles were identified: Belskiy-Filatov-Koplik spots (67.7%), staged eruption (100%), staged pigmentation (100%). Modern comprehensive therapy of young children with measles in combination with antioxidants (vitamins C and E) has significantly reduced the severity of complications, the frequency of the uneven course of the disease, and prevented the spread of acute respiratory viral infections